Modelling the distribution and abundance of several demersal fish species on the Agulhas Bank, South Africa - Sampson, Mark Robert (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2002)
The Agulhas Bank supports a speciose fish community, many of which are commercially important. Despite substantial research being conducted on aspects of their biology spatial aspects of their distribution and abundance in relation to environment parameters has been ignored. This study, therefore, addressed aspects related to the distribution and abundance of representative species on the Agulhas Bank within a Geographic Information System (GIS). Four candidate species were chosen due to their importance either in numbers or unit mass to the South African demersal trawl fishery. The species also shared morphological and taxonomic similarities. The candidate species chosen were the two Cape hake species, shallow-water hake Meluccius capensis, and deep-water hake Merluccius paradoxus, and the two pleuronectiform species being Agulhas sole Austroglossus pectoralis and redspotted tonguesole Cynoglossus zanzibarensis. The use of a GIS was appropriate and allowed for hidden spatial patterns be exposed and illustrated visually, while also facilitating the quantification of the relationships between distribution/abundance and certain environmental predictors using statistical methods The Department of Marine and Coastal Management, Cape Town, supplied biological data in the form of length frequency and biomass information from spring (AprillMay) and autumn (September/October) cruises conducted between 1986 and 1993 on the R. V. Africana. The Council for National Geoscience, Cape Town, supplied sediment data for the entire southern African coastline. Initial exploratory data analysis highlighted potential relationships between environmental variables and abundance for each specie's life-history stanzas. Variations in spatial distribution were found to be significantly different between each life-history stanzas within species. Fish density as a function of the additive effects of the various environmental parameters, including temperature, depth and sediment type, was assessed using a Poisson Generalized Additive Model (GAM), while distribution was analysed with a logistic GAM. A predictive logistic model was then created, taking into consideration the importance of the predictor variables for each species, allowing for predictive estimates to be made for each species by inputting environmental information within the study area. The importance of certain environmental variables influencing distribution and abundance were noted. General patterns indicated that sediment was the most important to both the distribution and abundance of the two pleuronectiform species and juvenile life-history stanzas, while the adult gadoids' distribution and abundance appeared to be depth dependent.
Keywords: Fishes -- South Africa -- Geographical distribution; Fishes -- South Africa -- Geographical distribution -- Mathematical models